Ethnicity as a Historical Process: An Appraisal on Patterns of Ethnogenesis in Nepal - Acharya, Pradeep (Historical Journal, 2020)
Ethnicity is a social and historical process, which carries changes and continuity simultaneously in different dimension of ethnic identity among the ethnic groups. Historical forces in terms of their social, political and economic dimension shape how ethnic identity is defined and created as well as recreated in contemporary society. Given the discussion this paper focuses on how the members of an ethnic group define themselves as a social group over time according to the social and political field in which they are in. The study has aims to describe the historical chronology of the transformation of Pahari identity over time in Nepal. Further, the paper particularly attempted to see how the political system of the country shapes the creation and recreation of identity among the members of the given ethnic group. The study is based on primarily on number of in-depth interviews of the members of the given ethnic community living in middle hills in and around around Kathmandu valley accompanied by available empirical literatures on ethnicity based on Nepal and abroad. The paper concludes that ethnicity and ethnic identity are not a stable entity rather it transforms as per social and political environment of the contemporary society.